A grounded theory inquiry of online freelance software developers - Lavilles, Rabby Q. (Animo Repository, 2018)
Online freelancing commonly known as online jobs in the perspective of the service providers has gained the attention of Filipinos as an alternative source of employment. In fact, the World Bank 2015 report in The Global Opportunity in Online Outsourcing states that, the Philippines has the largest proportion of working population engaged in online work. Motivated by this perspective, this study explores the experiences of online freelance software developers in the Philippines, particularly in Northern Mindanao. Using the classic grounded theory of Glaser, it was discovered that the main concern of online freelancers is earning flexibly in software development. Moreover, to continually resolve the main concern, they follow a basic social process of e-lancing work. e-Lancing work involves undergoing an iterative process of e-bidding and e-accomplishing through tasks or projects. The accumulated experiences throughout the iterative cycle resulted in a staged process including newbie, rockstar, and super-rockstar, which can be viewed as the professional life of online freelance software developers. Throughout the iterative and staged processes, strategies are employed via supporting information and communication technologies including circumtechventing to perform the job. The substantive theory of e-lancing work has implications for both the theory and practice including its utility as a framework for understanding the use of information technology and workarounds to earn flexibly in software development.